Pengaruh Keputusan Investasi, Pendanaan dan Dividen terhadap Nilai Perusahaan dengan Risiko sebagai Variabel Mediasi (Universitas Negeri Semarang, 2015)
The aim of this research is to know the influence of investment desicion, funding and dividend to the firm value with the risk as a mediation variable. Population that is used in this research is a company manufacturing sector which is listed on Indonesia Stock Exchange in the period from 2011 until 2013. Number of sample that used in this research is 60 samples with the method purposive sampling. Firm value variable is proxied by Price Book Value Ratio (PBR), Investment decision is proxied by Price Earning Ratio (PER), financing decision subtitued by Debt to Equity Ratio (DER), dividend policy is proxied by Dividend Pay Out Ratio (DPR) and business risk subtitued by Degree of Operating Leverage (DOL). Data Analysis using multiple regression analysis and line analysis by using a SPSS 16 program. The research concluded that only the investment decisions and the funding decision which has an effect on the firm value.